Some Mixed Ligand Complexes of Mn(III): Synthesis, Characterization and Application - Yadava, Sudha; Seema, (Asian Journal of Chemistry, 2010)
Few novel mixed ligand complexes of Mn(III) have been synthesised. These complexes are characterized by magnetic susceptibility, electronic conductivity and spectral (UV and IR) methods. The thermogravimetric studies have also been done. These complexes are with general formula [Mn(b-diketone)2X]2(en); b-diketone are acetylacetone, benzoylacetone, dibenzoylmethane; X = NCS–, N3 –, Cl–, Br– and en = ethylenediamine. These Mn(III) mixed ligand complexes are dimeric and bridged by ethylenediamine ligand. Azido complexes are bridges by the azido ligand also. Mn(III) is in six coordinated state. The magnetic moments for all these complexes indicate the presence of four unpaired electrons per manganese. The electronic conductivity data show the non-electrolytic nature for all the complexes. The TG study shows the absence of coordinated H2O molecule. Studies on six fungal strains and five bacterial strains have been done with these complexes and their antifungal and antibacterial properties are observed. Their role in conversion of high molecular weight coal fraction into low molecular weight coal fraction is also studied by viscosity measurement method and the results obtained show the delignification property for all these Mn(III) mixed ligand complexes.